Pepouza and Tymion: the discovery and archaeological exploration of a lost ancient city and an imperial estate - Tabbernee, William; Lampe, Peter (W. De Gruyter, 2008)
Early Christianity varied in appearance as much as the geography and terrain of the ancient Middle East. Often "variety" became pitted against "orthodoxy." Montanism, or the New Prophecy, was founded by a Phrygian named Montanus along with two ecstatic prophetesses, Maximilla and Priscilla. Even the North African Church Father Tertullian was a supporter of the New Prophecy movement. The Montanist variety of Christianity, however, soon fell into disfavor by those later deemed "orthodox", also because women played an influential role in this movement. Today we know